The Comparison Of Study Results In Accounting Learning Through Inside Outside Circle (Ioc) And Two Stay Two Stray (Tsts) Teaching Method - Casmudi, Casmudi (Opción, 2019)
This study aims to (1) analyze the difference between students’ exam results in accounting subject using cooperative learning model Inside Outside Circle (IOC) type and Two Stay Two Stray (TSTS) type, and (2) to evaluate which of the corresponding methods yields better result. The method used was qua- si-experimental research with control group; all two classes of eleventh-grade students of SMK Negeri 3 Balikpapan as subjects of the study of which meth- od was cluster random sampling; the data were collected through test and ob- servation, and the ınstruments’ validity, reliability, differential strength, and difficulty level received decent result; prerequisite tests including the average balance, normality, and homogeneity adhered to the proper criteria; the data analysis technique used for determining the difference between TSTS and IOC models in learning results was the z test, while the t-test was implement- ed to prove the effectiveness of the TSTS model compared to the IOC model. The research result shows that (1) there are significant differences in students’ learning results between the implementation of the IOC and TSTS models in accounting learning, indicated by the value of Zscore = 2.090> Ztable = 1.960 and (2) students’ learning results with the TSTS model are better than the IOC model, indicated by the value of t = 2.090> t table = 1.960. To sum up, there are differences in learning results between the IOC and TSTS models in accounting learning. The TSTS model is more effective than the IOC model in improving students’ learning results in accounting learning.